Diskursus Trend Teologi Baru Dalam Islam - Mustamin Giling (Foramadiahi: Jurnal Kajian Pendidikan dan Keislaman, 2019)
Islamic theology in developing this to be in accordance with the challenges and demands historical humanitarian step around him. Actual, context of work and formularization back problem of the godhead in islam that is associated with reality historical modern society. In other words, how changing face of conception who had been impressed defensive ( with only formularization ) to which is more dynamic, fresh, touching and also responsiveness to various issue of the godhead and diversity of today, stiff, was not impressed and only formalistik as well as a mere historica